Establishing universal sectioning depth and angle for surgical coronectomy of impacted mandibular third molars: an imaging-based study - Kamis Gaballah; Shishir Ram Shetty; Vinayak Kamath; Wael Talaat; Tara Renton (Frontiers Media S.A., 2024)
IntroductionCoronectomy is a safer option than extraction for third molars with an increased risk of injury to the inferior alveolar nerve. However, it can still cause complications due to a lack of standardized and effective tooth sectioning techniques. We proposed a standardized protocol for third molar coronectomy involving standardized tooth sectioning parameters to minimize potential complications, surgical failure, and the need for further procedures.MethodsThe study was conducted on 69 eligible archived CBCTs. The coronal sections of the mandibular at the anterior-most level of the lower third molar were used to determine various axes and reference points. This was done to establish the target angle and depth for the coronectomy sectioning. The data on the depth and angle of the sectioning was presented in means and standard deviation. A multivariate analysis of variance was used to determine the impact of study variables on drill depth and angle. Linear regression and correlation between study variables were also used to predict the drill depth and angle.ResultsThe samples included 46 males and 23 females aged from 21 to 47 years. The mean drill angle was determined as 25.01 ± 3.28. The mean drill depth was 9.60 ± 9.90 mm. The bucco-lingual tilt had a significant effect on the drill depth, F(1, 62) = 5.15, p < 0.05, but no significant impact on the drill angle, F(1, 62) = 29.62, p > 0.05. The study results suggest that a standardized sectioning protocol can be effective during surgical coronectomy procedures.DiscussionDrilling at a 25-degree angle to a depth of 9.5 mm is advisable to obtain the desired results. This approach will ensure no remaining enamel is left, minimize the chances of root extrusion and future eruption, and improve the outcome.